Communication Strategies Used by English Teacher in Teaching and Learning Process - Rofiatun, Iva (Universitas Muhammadiyah Semarang, 2018)
The aim of this study was to describe communication strategies employed by English teacher at a senior high school in central Java. Types of communication strategies and the function of communication strategies were included in this study. The subject of this study is an English teacher who taught eleventh grade at a senior high school in a central Java. This study belongs to qualitative study which involved observation and interview to collect the required data. Observation was conducted during English teaching and learning process to gain the detailed information about communication strategies used by English teacher. Then, interview was employed to clarify and enrich the data. The data were analyzed by using Dornyei & Scott?s (1997) taxonomy of communication strategies. The result of this study showed that there are six types of communication strategies used by English teacher during teaching and learning process. Code switching strategy was the most frequently used by English teacher during teaching and learning process. Those communication strategies were used to improve students? speaking ability and encourage them to communicate in English. In addition, teacher employed various communication strategies to stimulate students to be more active and confident in speaking during English teaching and learning process.